Evaluation of insulated gate bipolar transistor valve converter based unified power flow controller reliability and efficiency - Eniganti Sreeshobha; Raddymalla Linga Swamy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The effectiveness and reliability of the unified power flow controller (UPFC) are determined by the insulated gate bipolar transistor (IGBT) valve. Thermal losses, conduction losses, and switching losses in the IGBT valve all affect the efficiency of UPFC. The failure rate of the converter valves is influenced by junction temperature, which has an impact on the converter's reliability. Piecewise linear electrical circuit simulation (PLECS) was used to simulate two IGBT valve-based converter legs working at 12000 Hz, part number GT30F123. By reference to the switching characteristics produced by PLECS, switching losses, conduction losses, and thermal losses are analyzed. Simulation results are corroborated with analytical measurements. The chance of achieving 100%, 50%, and 0% functioning modes are among the reliability indices that are analyzed. The chance of achieving a hundred percent, fifty percent, or zero percent functioning mode is assessed. The frequency of achieving the state probability and mean time to failures (MTTF) are obtained from probabilities using the Markov model. The thermal losses, failure rate, and lifetime of the UPFC are all quantified to give a complete picture of the UPFC's performance.